PENERAPAN MODEL PEMBELAJARAN PROBLEM POSING UNTUK MENINGKATKAN KREATIVITAS - Dara Pusfita; Harina Fitriyani (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Students creativity in solving mathematical problems is lacking. When the teacher gives the problem, the students just doing as the teacher is example. So if the given problem is different from the already example, the students will have difficulty to solve it. This study aims to improve students creativity using problem posing model on the subject polyhedron.This study is classroom action research wich consistid of two cycles. The subject of this research is the students of class VIII C SMP Muhammadiyah 10 Yogyakarta in academic 2016/2017. The object of this research  is the improvement of students creativity. Data collection techniques such as observation, creativity test, and interview. Technique of data analysis was descriptife qualitative.The result showed that the problem posing method can improve students’ creativity of class VIII C. This can be seen from the average percentage of student observation results 1 cycle of 57,78% with sufficient criteria and in 2nd cycle increased to 83,05% with very good criteria. the average percentage of the results of assessment of student tests on the 1 cycle of 52,78% with sufficient criteria and in 2 nd cycle increased to 75,89 % with good criteria. Keywords: Improvement, Creativity, Problem Posing Model